Ody Salomona 29, 36, 40, 41 - Jutkiewicz, Piotr (Vox Patrum, 2021)
This paper presents a Polish translation from Syriac of four Odes of Solomon (29, 36, 40, 41), which have never yet been published in Polish. The translation is introduced by a short introduction and accompanied by a basic linguistic and theological commentary.